Scottish criminal justice: Devolution, divergence and distinctiveness. (April 2015) - Mooney, Gerry; Croall, Hazel; Munro, Mary; Scott, Gill
It has been claimed that paradoxically, following the re-establishment of the Scottish Parliament in 1999, Scottish criminal justice policy, hitherto more liberal and less punitive than 'south of the Border', became more closely aligned with London-based policies. It has also been argued that the Scottish Nationalist Party (SNP) Scottish government has, since gaining power in 2007, reversed that trend in a process of 'retartanization'. Closer examination reveals a far more complex picture. Based on interviews with key players and observers, this article suggests that there is room for a more nuanced understanding of policy, policy shifts and reform in the years leading up to and following 1999. The Scottish example raises important questions about the impact of new legislative and executive institutions, the respective influences of civil servants, special advisers, politicians, local government, media, public opinion and individual personalities on criminal justice policy, particularly in a small jurisdiction. It also raises questions about the relative importance of local, national, territorial and global influences on criminal justice policy of relevance to other devolved nations.